Odpowiedzi

2010-02-02T19:34:03+01:00
A) 2(3a-4b+c)-5(3a+b-2c)=6a-8b+2c-15a-5b+10c=-9a-13b+12c

b) 7(x+2y-3z)+4(2x-3y-5z)=7x+14y-21z+8x-12y-20z=15x+2y-41z

c) 2(a-3b)-3(a-b)-5(4a+3b)=2a-6b-3a+3b-20a-15b=-21a-18b

d) -3(2x-3y)+5(x+2y)-2(3y-x)=-6x+9y+5x+10y-6y+2x=x+13y
Najlepsza Odpowiedź!
2010-02-02T19:38:18+01:00
A) 2(3a-4b+c)-5(3a+b-2c)=6a-8b+2c-15a-5b+10c=-9a-13b+12c
b) 7(x+2y-3z)+4(2x-3y-5z)=7x+14y-21z+8x-12y-20z=15x+2y-41z
c) 2(a-3b)-3(a-b)-5(4a+3b)=2a-6b-3a+3b-20a-15b=-21a-18b
d) -3(2x-3y)+5(x+2y)-2(3y-x)=-6x+9y+5x+10y-6y+2x=1x+13y


;))))))))


aha i to rozwiązanie wyzej od tej innej osoby jest źle w punkcie c).


;P